MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) SISWA KELAS VI SD NEGERI 002 TELUK NILAP KUBU BABUSSALAM - Joeni Asih (Jurnal PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the low motivation of student learning in the lesson of Math class VI SD Negeri 002 Teluk Nilap Kubu Babussalam. This study aims to improve students' learning motivation in the lesson of Class VI SD Negeri 002 Teluk Nilap Kubu Babussalam by applying cooperative learning model of teams games tournament (TGT) type. The subjects of this study are all students of class VI SD Negeri 002 Teluk Nilap Kubu Babussalam which amounted to 29 people. The form of research is classroom action research. The instrument of this research consisted of performance instrument and data collection instrument in the form of observation sheet of teacher activity and student activity. Based on the results of analysis and discussion can be concluded that through cooperative learning model type TGT can improve students' learning motivation Math class SD Negeri 002 Teluk Nilap Kubu Babussalam students. Based on the results of the study note that the student's learning motivation before the action in a classical reach the average percentage of 36.2% is at the interval 0- 40%. The first cycle of the first meeting indicates that the students 'level of learning motivation classically only reaches the average 51.4% percentage in the 40% -55% interval is quite high and in the second meeting the students' learning motivation is classically reaching the percentage average of 56, 9%, are at a 40-55% interval quite high. While in the first cycle of the first encounter increased with the acquisition of the average value classically 71% are at intervals of 56% -75% are high and at the second meeting is klasikal get the average value of 83.4% percentage, is at interval 76- 100% with very high category.